Cardiovascular autonomic neuropathy and the risk of diabetic kidney disease - Cho, Injeong; Lim, Seohyun; Kwon, Minjae; Chung, Seung Min; Moon, Jun Sung; Yoon, Ji Sung; Won, Kyu Chang (Frontiers in Endocrinology, 2024)
Background: Cardiovascular autonomic neuropathy (CAN) is known to affect patients with diabetes mellitus (DM) and cause adverse renal outcomes. We aimed to analyze the association between CAN and diabetic kidney disease (DKD). Method: We enrolled 254 DM patients (mean age, 56.7±15.2 years; male: female ratio, 1.17:1) with 19 (7.5%) type 1 DM patients and 235 (92.5%) type 2 DM patients. All patients had undergone cardiovascular autonomic function tests between January 2019 and December 2021 in a tertiary hospital in Korea. Cardiovascular autonomic neuropathy was categorized as normal, early, or definite after measuring three heart rate variability parameters. Diabetic kidney disease refers to a persistently elevated urinary albumin-creatinine ratio (uACR ≥30 mg/g) or reduced estimated glomerular filtration rate (eGFR <60 mL/min/1.73 m2). Logistic and Cox regression analyses were performed. Results: Patients with elevated uACR (n=107) and reduced eGFR (n=32) had a higher rate of definite CAN. After adjusting for covariates, definite CAN was associated with elevated uACR (OR=2.4, 95% CI 1.07-5.36) but not with reduced eGFR (OR=3.43, 95% CI 0.62-18.90). A total of 94 patients repeated uACR measurements within 2 years (mean follow-up, 586.3±116.8 days). Both definite and early CAN were independent risk factors for elevated uACR (HR=8.61 and 8.35, respectively; both p<0.05). In addition, high-density lipoprotein cholesterol, ACE inhibitors/angiotensin receptor blockers and glucagon-like peptide-1 receptor agonists were independent protective factors for elevated uACR (HR=0.96, 0.25, and 0.07, respectively; all p<0.05). Conclusion: Cardiovascular autonomic neuropathy is a potential indicator of DKD. Comprehensive management of DKD in the early stages of CAN may prevent microalbuminuria.